Protein kinases as therapeutic targets to develop anticancer drugs with natural alkaloids - Hanlin Ye; Linlin Wang; Li Ma; Maksim Ionov; Gan Qiao; Jianlin Huang; Li Cheng; Yuxi Zhang; Xiaohui Yang; Shousong Cao; Xiukun Lin (Frontiers in Bioscience-Landmark, 2021)
Backgroud: Protein kinases play an important role in cell proliferation, differentiation, mobility and cell cycle arrest etc. These enzymes act as important targets in developing anticancer agents. Over the years, a large number of protein kinase inhibitors have been discovered and developed as anticancer agents for the treatment of cancers clinically. However, the drug-resiatance and off-targeting limit their effeciancy for the treatment of human cancer. Materials and methods: Alkaloids are an important class of natural products with broad spectrum biological activities. In the past decades, numerus alkaloids with significant anticancer activity by inhibiting protein kinases were identified. In the present mini-review, we will present the key enzymes including mitogen-activated protein kinase (MAPK), phosphoinositide 3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR) and janus-activated kinases/signal transducer and activator of transcription (JAK/STAT) targeted by alkaloids and highlight the special sites targeted by alkaloids on protein kinases and/or reversing drug resistance. Additionally, the challenge and prospect of developing alkaloids as new anticancer agents are also discussed. Conclusion: Alkaloids suppressed tumor growth through targeting different signaling pathways mediated by protein kinases of cancer cells. It is conceivable that novel alkaloids anticancer agents with promising clinical value will be developed in the future.